Soft power and higher education: an examination of China's Confucius Institutes - Yang, Rui (Globalisation, societies and education, 2010)
China's global presence has become a significant subject. However, little attention has been directed to the role of higher education in projecting China's soft power, and little academic work has been done directly on it, despite the fact that there has been some work on related topics. Borrowing the theories of soft power and higher education internationalisation, this article aims to fill in the gap in the literature by investigating China's projection of soft power via the conduit of recently established Confucius Institutes. Aiming to facilitate a more nuanced appraisal of China's global power and influence, it looks at Chinese higher education policy in a global context from the perspective of international power relations. Incorporating findings from an empirical case study of one Confucius Institute (based at a major Australian university) as a new distinctive model of international exchange and cooperation in higher education, this article looks at how Chinese universities interact with their international peers, in a context where China wants its universities to rival the best in the world, and invests heavily in its top universities.